The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.3389/fpsyt.2020.00365
|View full text |Cite
|
Sign up to set email alerts
|

Peer Support in Coordination of Physical Health and Mental Health Services for People With Lived Experience of a Serious Mental Illness

Abstract: Background: Engaging peer support to augment and enhance traditional mental health services presents novel opportunities to improve service engagement and delivery. However, there has not been an in-depth analysis of the processes and methods behind the coordination of physical health and mental health care by peer support specialists. Study aim: To explore the potential of peer support specialists in community mental health centers and as a means to improve coordination of physical health and mental health se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Similar findings have been found in peer engagement for youth program development [17]. Among adults, patient involvement in mental health and substance use settings reduced hospital readmission, increased patient well-being and engagement, and provided educational opportunities to health care staff and systems [18][19][20][21][22][23][24][25][26]. Lastly, several studies identified the importance of developing new processes of patient-oriented care, with the help of PWLE, rather than using existing practices with the hope that patients will adapt [27,28].…”
Section: Introductionmentioning
confidence: 63%
“…Similar findings have been found in peer engagement for youth program development [17]. Among adults, patient involvement in mental health and substance use settings reduced hospital readmission, increased patient well-being and engagement, and provided educational opportunities to health care staff and systems [18][19][20][21][22][23][24][25][26]. Lastly, several studies identified the importance of developing new processes of patient-oriented care, with the help of PWLE, rather than using existing practices with the hope that patients will adapt [27,28].…”
Section: Introductionmentioning
confidence: 63%
“…We included research articles that used diverse titles to label the positions or roles of people working with a lived experience background. Examples are “experts by experience” (Cooke et al, 2015 ; Jones & Pietilä, 2020 ), “peer providers” (Moran et al, 2012 , 2013 ; Siantz et al, 2016 , 2017 ; Zeng & Chung, 2019 ; Zeng et al, 2020 ), “peer support specialists” (Jenkins et al, 2020 ; Pantridge et al, 2016 ; Poremski et al, 2021 ), “peer support workers” (Collins et al, 2016 ; Nossek et al, 2021 ; Otte et al, 2019 ), “peer specialist” (Ahmed et al, 2015 ; Kuhn et al, 2015 ; Storm et al, 2020 ), and “peer workers” (Byrne et al, 2021b ; Gillard et al, 2015 , 2017 ; Marks et al, 2022 ; Oborn et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
“…Graduated peer counsellors, a new and rapidly growing profession already present in many addiction units, who can belong to medical teams at hepatology units as they already do, 71 could lower the threshold of engaging with peers, facilitate problem recognition and treatment adherence in patients with ALD, and improve stigmatising attitudes among healthcare professionals who would then experience working together with people in recovery. Involvement of trained people with lived experience in professional healthcare settings is common in mental healthcare, 74 and developing, evaluating and optimising such collaborative concepts in ALD care could be fruitful.…”
Section: Peer Involvementmentioning
confidence: 99%